Significant challenges when introducing care robots in Swedish elder care. (17th February 2022) - Johansson-Pajala, Rose-Marie; Gustafsson, Christine
Abstract: Introduction: Care robots are machines, operating partly or completely autonomously, that are intended to assist older people and their caregivers. Care robots are seen as one part of the solution to the aging population, allowing fewer professional caregivers to provide the necessary assistance and care. Despite the potential benefits, the dissemination of care robots, and welfare technology in general, is limited in Swedish elder care. Purpose: To explore the challenges of introducing welfare technology, particularly care robots, in elder care. Materials and methods: Twenty-one individual interviews with key actors at the societal level, analysed by thematic analysis. Results: The challenges, from the societal actors' perspectives, were related to; the beliefs in technology, attitudes, ethics, collaboration, and the need for knowledge and skills regarding care robots (individual and group challenges). Challenges of a national character were: national governance, infrastructure, laws and regulations, economics, and procurement (systemic and societal challenges). In addition, the necessary preconditions for successful introduction were revealed as: the utility of the technology, implementation, evaluation and safety, security, and integrity (preconditional challenges). Conclusions: The introduction of care robots in elder care services seems to be more challenging than that of welfare technology in general, given the context and prevailing attitudes and preconceptions about robotics. Significant challenges need to be managed, at all levels of the society, before care robots can become an integral part of daily care and assist older people and their caregivers in activities and rehabilitation. IMPLICATION FOR REHABILITATION: The challenges described by the societal actors', are partly similar to those of the end users', in terms of attitudes, ethics, knowledge and skills, and collaboration. This consensus should provide a solid foundation for the conceptualization and introduction of care robots in elderly care. The challenges follow the pattern of an ecosystem involving all sections of society, which are intertwined and require consideration before the expected benefits can be realised. A user-centred approach is necessary to support the design, implementation, and usefulness of care robots and their suitability for meeting the real needs of older persons and professional caregivers.